Seriously Considering Design in Educational Games. (December 2015) - Gaydos, Matthew
Research suggests that well-designed games can be good for learning under the right conditions. How such games are designed remains poorly understood, as studies have focused more on whether games can produce learning than on how such games work or how they can be reliably developed. That is, though the design of a game is considered essential to its effectiveness, educational games lack a theory-informed definition and have predominantly shared design in terms of "principles" or "heuristics." The aim of this paper is to discuss how we define and share educational game design and why design is important for improving educational game research and development.